Effect of superplasticizers on the rheological properties of fly ash incorporated cement paste. (2018) - Robert, C Rogin; Sathyan, Dhanya; Anand, K.B
Abstract: The rheology is a study of flow of matter. Rheological behavior of cement paste changes with composition of cement, amount of mineral and chemical admixtures, family of superplasticizer, temperature etc. This paper explores the influence of superplasticizer dosage, superplasticizer family and mineral admixture dosage on the rheological behavior of cement paste. For this purpose cement pastes were prepared at a water cement ratio of 0.37 using OPC and different percentage of fly ash (15, 25, 35) and different dosages of superplasticizer (one from each family). Four families of superplasticizer used for this study are polycarboxylate ether, sulphonate melamine formaldehyde, sulphonate naphthalene formaldehyde and lignosulphates. Rheological tests were performed in a coaxial cylinder viscometer (Brookfield DV-II). Saturation dosage of the superplasticizers in the cement paste mixes with different percentage of fly ash replacement were obtained through marsh cone and mini slump tests on cement paste. Cement pastes were placed in the sample chamber of coaxial cylinder viscometer and shear stress produced measured with known shear rate ranging from 30 S to 65 S -1 applied to the fluid through the spindle. Rheological parameters like yield stress and plastic viscosities were calculated using Bingham and Herschel bulkley model. Change in rheological parameters of the cement paste with fly ash replacement percentage, superplasticizers dosage and family were measured and comparison is made